2014
DOI: 10.1016/j.mri.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical exchange saturation transfer MRI using intermolecular double-quantum coherences with multiple refocusing pulses

Abstract: Chemical exchange saturation transfer (CEST) provides a new type of image contrast in MRI. Due to the intrinsically low CEST effect, new and improved experimental techniques are required to achieve reliable and quantitative CEST images. In the present work, we proposed a novel and more sensitive CEST acquisition approach, based on the intermolecular double-quantum coherence with a module of multiple refocusing pulses (iDQC-MRP). Experiments were performed on creatine and egg white phantoms using a Varian 7 T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Magnetization transfer (MT) imaging is a popular technique used in magnetic resonance imaging (MRI). Chemical exchange saturation transfer (CEST), a specific type of MT imaging, has recently emerged as an important contrast mechanism for MRI in the field of cellular and molecular imaging. It indirectly detects pools of exchangeable protons through the water signal from low-concentration exogenous or endogenous pools of exchangeable protons (such as amide or imino protons, amine protons, and hydroxyl protons) to the bulk water proton pool. , Irradiation offsets (ppm) around the water resonance frequency are set to acquire water signals. Therefore, MT spectra, also known as Z-spectra, are regarded as symmetric spectra around the water proton resonance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetization transfer (MT) imaging is a popular technique used in magnetic resonance imaging (MRI). Chemical exchange saturation transfer (CEST), a specific type of MT imaging, has recently emerged as an important contrast mechanism for MRI in the field of cellular and molecular imaging. It indirectly detects pools of exchangeable protons through the water signal from low-concentration exogenous or endogenous pools of exchangeable protons (such as amide or imino protons, amine protons, and hydroxyl protons) to the bulk water proton pool. , Irradiation offsets (ppm) around the water resonance frequency are set to acquire water signals. Therefore, MT spectra, also known as Z-spectra, are regarded as symmetric spectra around the water proton resonance.…”
mentioning
confidence: 99%
“…1−6 It indirectly detects pools of exchangeable protons through the water signal from low-concentration exogenous or endogenous pools of exchangeable protons (such as amide or imino protons, amine protons, and hydroxyl protons) to the bulk water proton pool. 7,8 Irradiation offsets (ppm) around the water resonance frequency are set to acquire water signals. Therefore, MT spectra, also known as Z-spectra, are regarded as symmetric spectra around the water proton resonance.…”
mentioning
confidence: 99%
“…The measured signal is generated from spins with distance equal to half of the length of the helix. Therefore, by changing the helix length, which is inversely proportional to the duration and strength of the gradient pulse, the interaction distance between spins is altered making this technique of interest for biological and clinical imaging ( 69),( 70), (71). Recently it was shown that the MT effect of immobilised molecules could be enhanced due to its large homogeneous broadening when saturation transfer experiments are combined with the iMQC method, in which the contrast is described by the m-th power where m is the quantum coherence order.…”
Section: Conceptmentioning
confidence: 99%
“…The iMQC effect has also been exploited in a preclinical system operating at 4.7T for imaging cartilage using solutions of glycosaminoglycans and cartilage tissue (71). In that case, the signal was shown to be equal to under a weak pulse approximation.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation